First Report, Characterization and Pathogenicity of Vibrio chagasii Isolated from Diseased Reared Larvae of Chilean Scallop, Argopecten purpuratus (Lamarck, 1819) - Rocío Urtubia; Claudio D. Miranda; Sergio Rodríguez; Javier Dubert; Juan L. Barja; Rodrigo Rojas (Pathogens, 2023)
Two Vibrio strains (VPAP36 and VPAP40) were isolated from moribund-settled larvae of the Chilean scallop Argopecten purpuratus during vibriosis outbreaks that occurred in two commercial scallop larvae hatcheries located in the Inglesa and Tongoy bays in Northern Chile. The strains were identified as Vibrio chagasii using phenotypic characterization and whole genome sequence analysis. Both strains exhibited the phenotypic properties associated with virulence, gelatin hydrolysis and β-hemolysis, whereas only VPAP36 produced phospholipase and only VPAP40 produced caseinase. The whole genome analysis showed that the strains harbored genes encoding for the virulence factors, the EPS type II secretion system, and Quorum Sensing (auto-inductor 1 and auto-inductor 2), whereas genes encoding a metalloproteinase and a capsular polysaccharide were detected only in the VPAP40 genome. When challenge bioassays using healthy 11-day-old scallop larvae were performed, the V. chagasii VPAP36 and VPAP40 strains exhibited significant (p < 0.05) differences in their larval lethal activity, producing, after 48 h, larval mortalities of 65.51 ± 4.40% and 28.56 ± 5.35%, respectively. Otherwise, the cell-free extracellular products of the VPAP36 and VPAP40 strains produced larval mortalities of 20.86 ± 2.40% and 18.37 ± 2.40%, respectively, after 48 h of exposure. This study reports for the first time the isolation of V. chagasii from the massive larval mortalities of the farmed scallop (Argopecten purpuratus) in Chile, and demonstrates the pathogenic activity of V. chagasii towards the Chilean scallop, the second most important species for Chilean mariculture.